Photoswitchable phthalocyanine-assembled nanoparticles for controlled "double-lock" photodynamic therapy. Issue 82 (26th September 2019) - Cheng, Hong-Bo; Li, Xingshu; Kwon, Nahyun; Fang, Yanyan; Baek, Gain; Yoon, Juyoung
Abstract : A new nanoparticle platform, NanoAzoPcS, is created by co-assembly of phthalocyanine and azobenzene amphiphiles, which can be used to gain precise control of PDT simply by regulating the stoichiometric ratio of the components and using light irradiation. Abstract : In the current study, a new nanoparticle platform, NanoAzoPcS, is created by co-assembly of phthalocyanine and azobenzene amphiphiles, which can be used to gain precise control of PDT simply by regulating the stoichiometric ratio of the components and using light irradiation. The results of antibacterial studies show that NanoAzoPcS serves as a smart PS for controlled PDT.